Women in the Boardroom: A Catalyst for Tax Avoidance? - Stanley, Nicklaus; Widianingsih, Luky Patricia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Tax is pivotal in a country’s economy because it is a nation’s largest source of income, However, taxpayers and the government have contrasting viewpoints regarding taxation. Taxpayers perceive taxation as a financial “burden” whereas the government considers tax as their source of revenue “revenue.” Due to the differing perspectives on taxation, taxpayers, especially firms, tend to resort to tax avoidance strategies to reduce their tax expenses. Therefore, the intent of this empirical study is to examine the effect of board gender diversity on corporate tax avoidance practices in the financial sector from 2021 to 2023 using the panel data regression approach. The results of this research study show that board gender diversity is associated with increased corporate tax avoidance practices. The controlled variables, firm size and leverage, do not significantly affect tax avoidance practices, whereas profitability has a significant positive effect. This result aligns with the critical mass theory in which a small proportion of female directors on the board cannot influence the decision-making process of a firm since they will just be ignored.